Effects of acid dopants on the capacitance of polyaniline by using graphene hydrogels as substrates. Issue 119 (18th November 2015) - Zhao, W.; He, D. W.; Wang, Y. S.; Hu, Y.; Du, X.; Hao, X.
Abstract : Acids have a great impact on the specific capacitance of polyaniline, and graphene/polyaniline (GP) doped with H2 SO4 possesses the highest capacitance compared with that of GP–HCl and GP–HClO4 . Abstract : Three kinds of polyaniline (PANI) doped with hydrochloric acid (HCl), sulfuric acid (H2 SO4 ) and perchloric acid (HClO4 ) were prepared separately by using graphene hydrogels as substrates, to investigate the influence of anions on the electrochemical properties of PANI for supercapacitors. The structures and polarities of the anions lead to differences in the morphology, oxidation state and crystallinity of PANI. The specific capacitances of the graphene/PANI (GP) composites doped with HCl, H2 SO4 and HClO4 are 303.8 F g −1, 464.1 F g −1 and 380.2 F g −1, respectively at a current density of 5 A g −1 . The capacitances of the three composites are retained at more than 98% at 70 A g −1 . The results exhibit that the acids have a great impact on the specific capacitance of PANI, and GP–H2 SO4 performs with the highest capacitance.